A Study of Local Government Website Inclusiveness: The Gap Between E-government Concept and Practice. Issue 1 (2nd January 2016) - Cumbie, Barry A.; Kar, Bandana
Abstract : This study examines the concept of electronic government (e-government) inclusiveness and evaluates the inclusiveness of local e-government websites. Inclusiveness sets e-government apart from other types of websites (e.g. commercial or organizational sites) that only serve exclusive market segments. An evaluation for inclusiveness of 101 local government websites from Mississippi (an underdeveloped area by many health and social metrics) revealed (1) a high frequency of issues that prevent inclusive service (on average each site had 291.83 issues), (2) high variability in terms of number of issues (range = [2, 3171]), and (3) widespread absence of websites (87 of the 188 municipalities and county seats did not have discoverable websites). These results suggest there is a need for more inclusiveness, but the allocation of resources to accomplish this may not be feasible. To address this, two strategic options are presented to information technology (IT) policy-makers who seek to leverage e-government for development: an idealistic approach with traditional IT investment for future returns and a pragmatic one that resembles an entrepreneurial IT start-up venture. The study contributes in three ways: we identify the concept and criteria of e-government inclusiveness; develop an automated, software-based, and replicable evaluation method that can be used by local governments to improve a website's inclusiveness; and present strategic options for using e-government to promote social and economic development.